2017
DOI: 10.1016/j.apergo.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Touchscreen interfaces in context: A systematic review of research into touchscreens across settings, populations, and implementations

Abstract: Although many studies have been conducted on the human factors and ergonomics (HFE) of touchscreens, no comprehensive review has summarized the findings of these studies. Based on a schema (three dimensions of understanding critical for successful display selection) presented by Wickens et al. (2004), we identified three dimensions of analysis for touchscreen implementations: touchscreen technology, setting and environment of implementation, and user population. We conducted a systematic review based on the PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Touch-screen input mimics a user’s natural way of interacting with the world and requires less cognitive burden than manipulating external input devices [19]. Usability studies have demonstrated that older adults complete tasks more quickly and with less errors on touch-screen devices in comparison to using a computer mouse [20,21]. Moreover, novice and expert older users of touch-screen devices complete tasks with similar low error rates [22].…”
Section: Methodsmentioning
confidence: 99%
“…Touch-screen input mimics a user’s natural way of interacting with the world and requires less cognitive burden than manipulating external input devices [19]. Usability studies have demonstrated that older adults complete tasks more quickly and with less errors on touch-screen devices in comparison to using a computer mouse [20,21]. Moreover, novice and expert older users of touch-screen devices complete tasks with similar low error rates [22].…”
Section: Methodsmentioning
confidence: 99%
“…The location of each device in relation to the user becomes an extremely important consideration; where increased levels of discomfort can arise where the user's arm needs to remain outstretched to interact with displays (Stanton et al, 2013, Shin andZhu, 2011;Wang and Trasbot, 2011;Dul and Weerdmeester, 2001). Orphanides and Nam (2017) recently performed the first review of studies that evaluated touchscreen interfaces with respect to their Human Factors and Ergonomic capabilities. They identified that selection for or against the use of touchscreens must take into account context of use to maximise safety, performance and user satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…These were drawn from Wickens et al, (2004) who identified these factors as key dimensions in display development and selection. One of the review criteria set by Orphanides and Nam (2017) in their assessment of the task dimension of touch screen use was the specific environments within which the touchscreen would enable the task to function. The review identified the use of touch screens in the road environment, extraneous moving environments, medical and other environments (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the last decade, touchscreen technology has been increasingly used not only across multiple types of devices, such as smartphones and tablets [1][2][3], but also in photocopying machines, automated teller machines (ATMs), and ticket machines in bus, railway stations, and airports. Reviews from the perspective of human factors and ergonomics and studies of people with developmental disabilities pointed out the relevance of the specific context of system interaction in order to maximize safety, performance, and user satisfaction [4] and the need for more research [5]. Touchscreens require the use of fingers and a choreography of gestures for interaction between the user and the device's user interface (UI) [6,7].…”
Section: Introductionmentioning
confidence: 99%